STUDENTS’ DIFFICULTIES IN ANSWERING READING COMPREHENSION QUESTIONS OF REPORT TEXT AT THIRD GRADE OF SMPN 1 BENGKULU SELATAN - Sepmi Risanda; Elfrida Elfrida; Kasmaini Kasmaini (Universitas Bengkulu, 2022)
This research aimed to find out the students difficulties in answering reading comprehension questions of report text and the causes of the students difficulties in answering reading comprehension questions of report text. The participants of this research were 63 third grade students at SMPN 1 Bengkulu Selatan. This research used descriptive quantitative as research design. The data were obtained through the reading comprehension test and interview section. The reading comprehension test was adapted from Mandiri textbook published by Tiga Serangkai consisted 25 questions of multiple choice. The reading comprehension test was validated by using the interpretation guidelines according to SPSS. In reliability obtains by using Cronbach’s Alpha formula in SPSS software. The result of this research showed that students faced some difficulties in answering reading comprehension questions of report text and there were some causes of their difficulties in answering reading comprehension questions of report text. The students difficulties in answering reading comprehension questions were locating pronouns, understanding vocabulary and making inference. Making inference became the most difficult aspect with percentage of students who answered questions about making inference incorrectly was 73%. The causes of students difficulties in answering reading comprehension questions of report text were lack of vocabulary, lack of strategies and lack of interest or motivation.